2020
DOI: 10.3389/fncel.2020.00057
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Environmental Enrichment Determines Astrocyte Number and Cervical Lymph Node T Lymphocyte Proportions but Not the Microglial Number in Middle-Aged C57BL/6 Mice

Abstract: Environmental enrichment (EE) has been shown to modulate behavior and immunity. We recently reported that both short and long-term EE enhance baseline locomotion and alleviate depressive-like behavior, but only long-term EE affects locomotion adversely in a threatening environment and enhances anxiety-like behavior in middle-age mice. We have now investigated whether the observed changes in behavior after short-and long-term EE were associated with underlying immune changes. Hence, at the end of behavioral tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Intriguingly, we observed a significant increase in adult astrogenesis upon running wheel stimulus, which was driven by increased proliferation of local astrocytes. Together with evidence that enriched environment, another pro‐neurogenic stimulus, evokes a similar increase in astrogenesis (Williamson et al , 2012; Singhal et al , 2020), our data suggest that adult astrogenesis is a dynamic process able to adapt to environmental stimuli (Fig 7B). However, even though total numbers increased, the percentage of neurons and astrocytes among all newly generated cells did not differ between standard housing conditions and running wheel.…”
Section: Discussionsupporting
confidence: 86%
“…Intriguingly, we observed a significant increase in adult astrogenesis upon running wheel stimulus, which was driven by increased proliferation of local astrocytes. Together with evidence that enriched environment, another pro‐neurogenic stimulus, evokes a similar increase in astrogenesis (Williamson et al , 2012; Singhal et al , 2020), our data suggest that adult astrogenesis is a dynamic process able to adapt to environmental stimuli (Fig 7B). However, even though total numbers increased, the percentage of neurons and astrocytes among all newly generated cells did not differ between standard housing conditions and running wheel.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies have shown that environmental enrichment including voluntary exercise and somatomotor and visuospatial stimulation is capable of promoting the modulation of cytokines (Pedersen, 2009) and chemokines (Trøseid et al, 2004), natural killer cells (Benaroya‐Milshtein et al, 2004), and T lymphocytes mobilization (Marashi, Barnekow, Ossendorf, & Sachser, 2003; de Sousa et al, 2011; Singhal et al, 2020), microglia (Gomes et al., 2019; de Sousa et al., 2015) and astrocytes numerical and morphological changes (Diniz et al, 2010; Diniz, Silva, et al, 2016; Leardini‐Tristão et al, 2020; Singhal et al, 2020) and neurogenesis (Valero, Paris, & Sierra, 2016; Wasinski, Batista, Bader, Araujo, & Klempin, 2018). Bi‐directional cross talk between microglia, astrocytes and neurons (Singhal et al, 2020; Kofuji & Araque, 2020) are key elements to achieve homeostatic conditions, and chemokine signaling seems to be essential to orchestrate communication among them, preserving brain function (Trettel, Di Castro, & Limatola, 2019). The morphometric studies of the present work compared the microglial morphology of elderly mice kept in impoverished cages with that of the same age animals kept in enriched cages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also shown that short duration moderate exercise can improve survival in mice infected with a lethal dose of influenza virus (177). It has been shown that environmental enrichment and physical exercise, when combined, reduce brain cytokine expression (178), which may contribute to this outcome. Consistent with these findings, 6-month old mice under environmental enrichment, subjected to the neurotropic Piry arbovirus infection, increase T-cell infiltration and show less CNS cell infection by the virus and/or faster virus clearance, less microgliosis, and less damage to the extracellular matrix, than infected mice maintained in standard laboratory cages (27).…”
Section: Age and Sedentary Lifestyle Reduce Microglial Morphological Reactivity Under Neurotropic Arbovirus Infectionmentioning
confidence: 99%
“…differentiated effector memory T-cells, weak proliferative responses to mitogenic agents, and a ratio of CD4 to CD8 lymphocytes of less than 1.0 (179). Physical exercise and environmental enrichment can modulate immunity in aged humans (180,181) and in experimental models (15,27,178,182,183). Indeed, it has been suggested that exercise might exert an anti-immunosenescence effect, delaying the onset of immunological ageing and rejuvenating aged immune profiles (179).…”
Section: A B D Cmentioning
confidence: 99%